Chemolithoautotrophic arsenite oxidation by a thermophilic Anoxybacillus flavithermus strain TCC9-4 from a hot spring in Tengchong of Yunnan, China - Jiang, Dawei; Li, Ping; Jiang, Zhou; Dai, Xinyue; Zhang, Rui; Wang, Yanhong; Guo, Qinghai; Wang, Yanxin (Frontiers in Microbiology, 2015)
A new facultative chemolithoautotrophic arsenite (AsIII)-oxidizing bacterium TCC9-4 was isolated from a hot spring microbial mat in Tengchong of Yunnan, China. This strain could grow with AsIII as an energy source, CO2–HCO3- as a carbon source and oxygen as the electron acceptor in a minimal salts medium. Under chemolithoautotrophic conditions, more than 90% of 100 mg/L AsIII could be oxidized by the strain TCC9-4 in 36 h. Temperature was an important environmental factor that strongly influenced the AsIII oxidation rate and AsIII oxidase (Aio) activity; the highest Aio activity was found at the temperature of 40∘C. Addition of 0.01% yeast extract enhanced the growth significantly, but delayed the AsIII oxidation. On the basis of 16S rRNA phylogenetic sequence analysis, strain TCC9-4 was identified as Anoxybacillus flavithermus. To our best knowledge, this is the first report of arsenic (As) oxidation by A. flavithermus. The Aio gene in TCC9-4 might be quite novel relative to currently known gene sequences. The results of this study expand our current understanding of microbially mediated As oxidation in hot springs.